2007
DOI: 10.1017/s0950268807008060
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a school-based safe water and hygiene programme on knowledge and practices of students and their parents: Nyanza Province, western Kenya, 2006

Abstract: The impact of a school-based safe water and hygiene programme on knowledge and practices of students and their parents: Nyanza Province, western Kenya, 2006. Epidemiology and infection, 136 (1 The impact of a school-based safe water and hygiene programme on knowledge and practices of students and their parents: Nyanza Province, western Kenya, 2006 SUMMARYSafe drinking water and hygiene are essential to reducing Kenya's diarrhoeal disease burden. A school-based safe water and hygiene intervention in Kenya was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
116
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(138 citation statements)
references
References 29 publications
20
116
1
1
Order By: Relevance
“…The above findings are almost similar to the studies of Tragler [14] and Fawole et al [15] in which significant increase in KAP after the experiment (health education) was observed. The proportion of correct answers reported among mothers is similar to study conducted by Danielle Ferreira de Magalhães et al [9] which observed the less proportion of correct answers by family members. …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The above findings are almost similar to the studies of Tragler [14] and Fawole et al [15] in which significant increase in KAP after the experiment (health education) was observed. The proportion of correct answers reported among mothers is similar to study conducted by Danielle Ferreira de Magalhães et al [9] which observed the less proportion of correct answers by family members. …”
Section: Discussionsupporting
confidence: 88%
“…Majority of them were boys constituting 74.7% in the study group and 70.7% in control group whereas only about 1/4 th girl's population was constituted in study and control group (25.3% and 29.3%, respectively). In a study of Danielle Ferreira de Magalhães et al [9] students from the 5 th and 8 th grades were participants of the study. Mean age was 10 years (range: 9-14) in the 5 th grade and 14 years (range: 13-17) in the 8 th grade.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with the previous studies that found lower rates of total absenteeism after the implementation of school WASH programs. 10,15,22 The fact that we found no effect modification based on sex rules out differential impacts among girls, as found in Kenya. 15 Although it is possible that the increased absence observed in the beneficiary schools was due to some aspect of the delivery of the intervention, it is more likely that this difference was due to suboptimal matching of comparison schools.…”
Section: Discussionsupporting
confidence: 52%
“…The magnitude of these changes exceeded that of an earlier school program in the same region. 7 There are several possible explanations for the observed increases in water treatment knowledge and practices. First, schools are known to be effective venues to teach new educational material, as indicated by the finding that schools became the main information source about water treatment cited by both students and their caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of this program in 2006 suggested that the use of water treatment and hand-washing promotion in schools resulted in a decrease in absenteeism of 35% compared with neighboring schools, and increased utilization of WaterGuard in students' households. 7 The outcomes of these two projects have resulted in further expansion of the school programs in Nyanza Province. 8 In 2000, the Procter and Gamble Company (Mason, OH) launched a flocculent/disinfectant product, called PuR ® Purifier of Water (hereafter referred to as PuR ® ) which was designed for household water treatment.…”
Section: Introductionmentioning
confidence: 99%